A study of prevalence of asymptomatic bacteriuria in pregnant women from rural areas attending to Obstetric Department in Akash Hospital, Karnataka, India - S., Rohini N.; N., Ravishankar S.; K., Kala; R., Rakshith N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Asymptomatic bacteriuria (ASB) in pregnancy is a significant risk factor for developing upper urinary tract infection and pyelonephritis which is associated with significant maternal and fetal risks. The aim of this study was to know the prevalence of asymptomatic bacteriuria in pregnancy, to identify the organisms and their antibiotic susceptibility patterns and to formulate a single or combined rapid screening method as an acceptable alternative to urine culture. Methods: A total of 375 pregnant women aged between 18 to 45 years were included in this study. Clean catch mid-stream urine samples were collected. Screening tests done were gram staining of uncentrifuged urine, pus cell count, nitrite test and leukocyte esterase test. Identification of pathogens and antibiotic sensitivity tests were performed as per standard urine culture and sensitivity methods. Results: Out of the 375 pregnant women, 31 (8.4%) had significant bacteriuria. High percentage of women with ASB were primigravidas (51.38%) and in 2nd trimester (43.86%). The most common organism isolated was E.coli (56.14%). In screening tests, gram staining of uncentrifuged urine had a sensitivity of 85.71%. Sensitivity of 71.42% was found in Nitrite and leucocyte esterase tests. However, the combination of these two tests, with either test positive, showed sensitivity and negative predictive value of 90.47% and 99.09% respectively. Conclusions: Early detection and treatment of ASB in pregnancy can prevent complications. ASB can be identified by simple and combined rapid screening methods and urine culture along with antibiogram. Therefore, screening and treatment of ASB may be incorporated as routine antenatal care for safe motherhood and healthy newborn.